2013
DOI: 10.1017/s0013091513000369
|View full text |Cite
|
Sign up to set email alerts
|

Cohomological finiteness properties of the Brin–Thompson–Higman groups 2V and 3V

Abstract: Abstract. We show that Brin's generalisations 2V and 3V of the Thompson-Higman group V are of type FP∞. Our methods also give a new proof that both groups are finitely presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…This is exactly the condition that proved difficult to verify for the filtration of |P 1 | in [KMPN10].…”
Section: The Stein Space For Svmentioning
confidence: 92%
See 1 more Smart Citation
“…This is exactly the condition that proved difficult to verify for the filtration of |P 1 | in [KMPN10].…”
Section: The Stein Space For Svmentioning
confidence: 92%
“…These groups are usually termed higher-dimensional Thompson's groups or Brin-Thompson groups. All of the groups sV are known to be finitely presented [HM12], and Kochloukova, Martínez-Pérez, and Nucinkis [KMPN10] showed that 2V and 3V are of type F ∞ . We prove that this result extends to all dimensions.…”
mentioning
confidence: 99%
“…By using his method, we proved that the topological full group [[G A ]] of any SFT groupoid G A is of type F ∞ ([28, Theorem 6.21]). As for the higher dimensional Thompson groups, D. H. Kochloukova, C. Martínez-Pérez and B. E. A. Nucinkis [22] showed that 2V 2,1 and 3V 2,1 are of type F ∞ . This was later generalized to all nV 2,1 by M. Fluch, M. Marschler, S. Witzel and M. C. B. Zaremsky [12].…”
Section: Classificationmentioning
confidence: 99%
“…The three Thompson groups F , T , and V have type F ∞ [4,7], as do many of their variants such as the generalized groups F n,k , T n,k and V n,k [4], certain diagram groups [12] and picture groups [14], braided Thompson groups [8], higher-dimensional groups nV [16,20], and various other generalizations [1,10,11,15,21,22].…”
Section: Introductionmentioning
confidence: 99%